Berlin 750 - 750 Jahre Berlin 1987 : Schilderkunst, beeldhouwkunst, grafiek, tapijtkunst. - Coucke, Jo; Gele Zaal, Gent (Otegem : Deweer Art Gallery, 1987)
Bach, Elvira ; Castelli, Luciano ; Dornseif, Frank ; Endart ; Fetting, Rainer ; Hacker, Dieter ; Hodicke, Karl Horst ; Koberling, Bernd ; Lange, Thomas ; McLean, Bruce ; Middendorf, Helmut ; Penck, A.R. ; Salome
Berlin 750 - 750 Jahre Berlin 1987 : schilderkunst, beeldhouwkunst, grafiek, tapijtkunst, Deweer Art Gallery, Otegem (Zwevegem), 7.2 - 8.3.1987 ; Gele Zaal, Gent
Nederlands & Frans
kunstcatalogus
Keywords: Berlijn